A Review of Measurement Techniques of Mechanical Properties of the Catalyst Layer in Catalytic Converters. Issue 3 (1st July 2019) - Yang, Jiankai; Salman, Agba D.; Blanco-García, Patricia
A catalyst support is often used to disperse a catalyst material to enhance the contact area for reaction. In catalytic converters, a coating called the catalyst layer contains both the catalyst support and catalytically active material. Given the role of the catalyst layer in catalytic converters, its mechanical strength is of great importance as it determines the service life of catalytic converters. This review paper therefore summarises a number of methods which are currently used in the literature to measure the strength of a catalyst layer. It was identified that the methods applied at present could be divided into two groups. All methods regardless of the group have been successfully used to investigate the effect of a range of formulation and process parameters on the strength of a catalyst layer. In terms of measurement principles, Group 1 methods measure the strength based on mass loss after the layer sample is subjected to a destructive environment of choice. Group 2 methods tend to give more direct measurements on the strength of bonding between particles in a catalyst layer. Therefore, strength data generated by Group 2 methods are more reproducible between different researchers as the results are less dependent on the testing environment. However, methods in both groups still suffer from the fact that they are not designed to separately measure the cohesive and the adhesive strength of a catalyst layer. Two new methods have been recently proposed to solve this problem; with these methods, the cohesive and adhesive strength of a catalyst layer can be measured separately.